Edukasi Kesehatan Reproduksi Remaja dalam Upaya Mencegah Perilaku Seksual Berisiko di Kota Palangka Raya - Sukriani, Wahidah; Wahyuni, Seri (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Adolescence is a transition period towards adulthood. During this period, risky sexual behavior often occurs. Palangka Raya is the capital of Central Kalimantan Province which is the third highest in child marriages in Indonesia. Information and education regarding inappropriate and correct sexuality as well as hidden messages in exposure to media containing pornographic content will increase teenagers' interest in premarital sex which can increase cases of child marriage. This community service activity aims to provide education to teenagers to understand reproductive health so that they can prevent and avoid risky sexual behavior. The method of implementing the activity is by giving a pretest, providing education about reproductive health and preventing risky sexual behavior in two stages, discussion and giving a posttest about adolescent knowledge about reproductive health to 30 activity participants. This activity was carried out at the Antang Bajenta youth posyandu in September 2022. The results of the activity showed that there was an increase in knowledge in the good category, from 13.3% to 76.7%. The conclusion is that this activity can increase teenagers' knowledge by 63.4%. It is hoped that this programs can be carried out regularly by health workers both at school and outside school, such as at youth posyandu and other youth activities.